Ocular Biocompatibility of Nitinol Intraocular Clips - Olson, Jeffrey L. (Association for Research in Vision and Ophthalmology, Inc., 2012)
PURPOSE. To evaluate the tolerance and biocompatibility of a preformed nitinol intraocular clip in an animal model after anterior segment surgery. METHODS. Yucatan mini-pigs were used. A 30-gauge prototype injector was used to attach a shape memory nitinol clip to the iris of five pigs. Another five eyes received conventional polypropylene suture with a modified Seipser slip knot. The authors compared the surgical time of each technique. All eyes underwent standard full-field electroretinogram at baseline and 8 weeks after surgery. The animals were euthanized and eyes collected for histologic analysis after 70 days (10 weeks) postsurgery. The corneal thickness, corneal endothelial cell counts, specular microscopy parameters, retina cell counts, and electroretinogram parameters were compared between the groups. A two sample t-test for means and a P value of 0.05 were use for assessing statistical differences between measurements. RESULTS. The injection of the nitinol clip was 15 times faster than conventional suturing. There were no statistical differences between the groups for corneal thickness, endothelial cell counts, specular microscopy parameters, retina cell counts, and electroretinogram measurements. CONCLUSIONS. The nitinol clip prototype is well tolerated and showed no evidence of toxicity in the short-term. The injectable delivery system was faster and technically less challenging than conventional suture techniques.